Interorganizational cost management in a glass container manufacturing company (Costos y Gestión, 2025)
The objective of the research was to analyze the five determinant factors for the practice of Interorganizational Cost Management (ICM) in a glass container manufacturing company. An exploratory, descriptive and qualitative research was carried out using a questionnaire and a semi-structured interview with the person in charge of cost management to gather information. The results of the research allow identifying evidence on the applicability of the ICM for its five determinant factors. It was concluded that for the component dimension, the application of  ICM would be remote, since the company has a high technological restriction and a value index higher than 1, which means that any change in the characteristics of its products has a significant effect on the perception of customers and its effect on the final cost of the product is insignificant, however, despite the fact that not all dimensions are favorable for the application of ICM, it is verified that Interorganizational Cost Management is possible and desirable, creating strategic alliances with customers and suppliers, with joint cost reduction goals and mutual benefit sharing.
Keywords: Inter-organizational cost management; Strategic cost management; Costing; Open book accounting